MALDI-TOF MS: foundations and a practical approach to the clinically relevant filamentous fungi identification - Gómez-Velásquez, Juan C. (2021)
In this review, the applicability of matrix-assisted laser ionisation/desorption time-of-flight mass spectrometry (MALDI-TOF) to the identification of clinical relevant filamentous fungi is presented. In addition, the need to implement and validate in-house databases, to fill the gaps in commercial databases, and the importance of permanently updating spectra databases are topics addressed.